Critical Synthesis Package: Depression Anxiety Stress Scales (DASS) - Era Buck (Association of American Medical Colleges, 2014)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the Depression Anxiety Stress Scales (DASS), and (2) a copy of both the 42− and 21-item Depression Anxiety Stress Scales instrument and scoring guides developed by Peter Lovibond, PhD. The Depression Anxiety Stress Scales (DASS) is available in 42− and 21-item versions with a 4-point, Likert-type response scale. It is a self-report measure providing a total score as well as subscores for depression, anxiety, and stress. The DASS is intended for both clinical and research use, may be administered to individuals or groups, and is appropriate for single or repeated use. The psychometric properties have been examined in a variety of settings and populations with very consistent results indicating this measure provides a strong measure of these constructs. Extensive psychometric exploration has provided consistent support for the validity in both clinical and non-clinical populations. It has been successfully employed in medical education research as a measure of learner wellbeing and a source of personal information for reflection. However, since a primary concern for this instrument is that it is transparent and has no safeguard against faking, students who doubt the anonymity of their responses may be reluctant to answer truthfully. Medical educators using this instrument need to take measures to ensure that students feel safe to provide truthful answers. The shorter version (DASS-21) presents a minimal response burden while preserving the psychometric strengths of the original version.